Rosiglitazone Regulates Anti-Inflammation and Growth Inhibition via PTEN. (13th March 2014) - Lin, Chiou-Feng; Young, Kung-Chia; Bai, Chyi-Huey; Yu, Bu-Chin; Ma, Ching-Ting; Chien, Yu-Chieh; Chiang, Chiu-Ling; Liao, Chao-Sheng; Lai, Hsin-Wen; Tsao, Chiung-Wen
Abstract : Peroxisome proliferator-activated receptor gamma (PPARγ ) agonist has anti-inflammatory and anticancer properties. However, the mechanisms by which PPARγ agonist rosiglitazone interferes with inflammation and cancer via phosphatase and tensin homolog-(PTEN)-dependent pathway remain unclear. We found that lower doses (<25  μ M) of rosiglitazone significantly inhibited lipopolysaccharide-(LPS)-induced nitric oxide (NO) release (via inducible nitric oxide synthase, iNOS), prostaglandin E2 (PGE2 ) production (via cyclooxygenase-2, COX-2), and activation of Akt in RAW 264.7 murine macrophages. However, rosiglitazone did not inhibit the production of reactive oxygen species (ROS). In PTEN knockdown (shPTEN) cells exposed to LPS, rosiglitazone did not inhibit NO release, PGE2 production, and activation of Akt. These cells had elevated basal levels of iNOS, COX-2, and ROS. However, higher doses (25–100  μ M) of rosiglitazone, without LPS stimulation, did not block NO release and PGE2 productions, but they inhibited p38 MAPK phosphorylation and blocked ROS generation in shPTEN cells. In addition, rosiglitazone caused G1 arrest and reduced the number of cells in S + G2/M phase, leading to growth inhibition. These results indicate that the anti-inflammatory property of rosiglitazone is related to regulation of PTEN independent of inhibition on ROS production. However, rosiglitazone affected the dependence of PTEN-deficient cell growth on ROS.